2019
DOI: 10.4018/978-1-5225-6322-8.ch013
|View full text |Cite
|
Sign up to set email alerts
|

Promising Practices in Online Training and Support

Abstract: With increasing visibility for all educators to meet technology standards, teacher educators must prepare their teacher candidates for the increasing demand for education technology integration in preK-12 and higher education classrooms. Many university faculty, who are responsible for this preparation of teachers, feel unprepared for this challenge, which often pushes them out of their comfort zone. As teacher educators in a small university in Southern Texas, the authors explored specific engagements that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Many studies revealed that gamification and microlearning positively affected the participants’ experience, attitude, and knowledge acquisition. 9,19,20…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies revealed that gamification and microlearning positively affected the participants’ experience, attitude, and knowledge acquisition. 9,19,20…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed that gamification and microlearning positively affected the participants' experience, attitude, and knowledge acquisition. 9,19,20 Most studies had small samples with no control groups making them difficult to generalize their results. 21,22 A recent meta-analysis demonstrated that effects of gamification on cognitive learning outcomes are more stable than the effects on behavioral or motivational outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microlearning enables learners to reduce information overload, enrich learning processes, improve training effectiveness, and increase learners' level of engagement in online environments (Nikou and Economides 2018;Shamir-Inbal and Blau 2020). This is because it aids better retention thus allowing learners to develop self-regulation skills and lifelong learning capacities (Aldosemani 2019;Reinhardt and Elwood 2019).…”
Section: Introductionmentioning
confidence: 99%